Tworzenie podstaw trwałego wzrostu gospodarczego przez politykę makroekonomiczną w Polsce w okresie transformacji - Klamut, Mirosława (Polish Macroeconomic Policy in the Period of Transition and Supporting Constant Economic Growth, 2005)
The paper points to the conditions of choosing a demand-oriented model of economic policy in Poland in the period of joining the euro zone, and also after it. The author claims that inflation processes in the economy were brought under control by the monetary policy. Improvements in the fiscal policy and in real structural economic changes both enhance the possibility of entering the euro zone. As its member, Poland becomes a credible economic partner in the European and world markets. It enables raising investment rate due to the foreign cash inflow. It is necessary for the Polish economy to become more competitive. Joining the euro zone soon is a chance to boost the economic growth in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 13-22